Administration of Etlingera hemisphaerica Fruit Juice on the Recovery of Glucose Levels Due to HgCl₂ Treatment in Mice (Mus musculus ) - Davina Shava Ferlia; Aceng Ruyani; Deni Parlindungan; Annisa Puji Astuti; Afrizal Mayub (Jurnal FARMASIMED (JFM), 2025)
Background: Fruit juice is highly needed nowadays due to its effectiveness as a source rich in antioxidants.Research Objective: This study aims to reduce glucose levels caused by the administration of HgCl₂, which is neurotoxic and cytotoxic, capable of damaging pancreatic β-cells that produce insulin. Etlingera hemisphaerica was utilized as a potential solution because it contains compounds such as terpenoids, flavonoids, phenols, and polyphenols that can lower glucose levels by maintaining the normal function of pancreatic β-cells. Method: This study applied a true experimental method with a pretest-posttest control group design, involving measurements taken before and after treatment. The subjects were divided into three test groups K1, K2, and K3 each consisting of three Mus musculus , with a total of nine mice. Results: The administration of Etlingera hemisphaerica Fruit Fresh Drink (MSBE) did not show a significant effect in reducing blood glucose levels in Mus musculus  induced with HgCl₂. Conclusion: The secondary metabolites contained in E. hemisphaerica  have not yet been able to repair or maintain blood glucose levels under conditions of damage caused by HgCl₂ exposure.